2020
DOI: 10.1021/acs.langmuir.9b03487
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Actuation of Surface Walkers: The Effects of Confinement and Inertia

Abstract: Driven by a magnetic field, the rotation of a particle near a wall can be rectified into a net translation. The particles thus actuated, or surface walkers, are a kind of active colloid that finds application in biology and microfluidics. Here, we investigate the motion of spherical surface walkers confined between two walls using simulations based on the immersed-boundary lattice Boltzmann method. The degree of confinement and the nature of the confining walls (slip vs no-slip) significantly affect a particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…A counterclockwise rotating microroller at a fixed position always experiences forces in negative direction without hydrodynamic confinement effects (32,36). However, when the channel is confined beyond a certain threshold, magnitude of this force could decrease and eventually reverse in direction according to numerical simulations (36). We also observed the confinement effect in our simulations, in which a single microroller experienced positive total force, despite rotating counterclockwise in a 75 μm high microchannel.…”
Section: Engineeringsupporting
confidence: 56%
See 1 more Smart Citation
“…A counterclockwise rotating microroller at a fixed position always experiences forces in negative direction without hydrodynamic confinement effects (32,36). However, when the channel is confined beyond a certain threshold, magnitude of this force could decrease and eventually reverse in direction according to numerical simulations (36). We also observed the confinement effect in our simulations, in which a single microroller experienced positive total force, despite rotating counterclockwise in a 75 μm high microchannel.…”
Section: Engineeringsupporting
confidence: 56%
“…Other than microtopographies, flow fields generated by microrollers also interact with the narrow-channel boundaries, which could create additional resistive forces on the microrollers. A counterclockwise rotating microroller at a fixed position always experiences forces in negative direction without hydrodynamic confinement effects (32,36). However, when the channel is confined beyond a certain threshold, magnitude of this force could decrease and eventually reverse in direction according to numerical simulations (36).…”
Section: Engineeringmentioning
confidence: 99%
“…The quick response characteristic of a ferrofluid upon the magnetic field makes it an attractive medium to manipulate droplets. Although many researchers have adopted the active magnetic field to manipulate the mobility and deformability of the ferrofluid droplet [9][10][11][12], few studies have reported on how the morphology evolution of ferrofluid droplets affects their subsequent freezing process. In this study, the morphology of ferrofluid droplets is manipulated by imposing an external magnetic field to control their freezing processes.…”
Section: Introductionmentioning
confidence: 99%
“…2018 b ; Fang et al. 2020). Third, our results reveal an interesting feature that the induced translation occurs in the negative -direction (referred to as the backward mode in this work), opposite to what might be intuitively expected for an object rolling along a solid surface.…”
Section: Resultsmentioning
confidence: 99%